2016
DOI: 10.1111/2041-210x.12649
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in spatial utilization distributions measured by the earth mover's distance

Abstract: Summary1. Estimating the similarity in space use (spatio-temporal home range overlap) of animals is important for many questions regarding behavioural ecology, wildlife management and conservation. The current methods that calculate joint space use generally do not account for proximity in space use, as all of them rely on the differences between the exact spatial overlay of utilization distributions, while spatial distances between distributions should be considered to truly quantify similarity. 2. We impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…In contrast, we use in this study a more general null model, comparing the observed migrations to alternative simulated migrations. Our result that the observed thermal distance across seasons (computed using the Earth Mover's Distance; Kranstauber et al 2016) appears to perform well when compared the alternative options (Fig. 2B) thus provide evidence for tracking of temperature conditions via migration.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, we use in this study a more general null model, comparing the observed migrations to alternative simulated migrations. Our result that the observed thermal distance across seasons (computed using the Earth Mover's Distance; Kranstauber et al 2016) appears to perform well when compared the alternative options (Fig. 2B) thus provide evidence for tracking of temperature conditions via migration.…”
Section: Discussionmentioning
confidence: 57%
“…For each species, we then measured the inter-seasonal thermal distance by computing the Earth Mover's Distance (EMD) between the breeding and non-breeding probability distribution landscapes in the general temperature space. The EMD is an algorithm that was originally developed for image comparison (Rubner et al 2000) and has been recently adapted to quantify similarity between spatial utilization distributions (Kranstauber et al 2016). It provides a distance measure by calculating the effort it takes to shape one probability distribution landscape into another.…”
Section: Measuring Inter-seasonal Thermal Distancementioning
confidence: 99%
See 1 more Smart Citation
“…A more recently developed method, earth mover's distance, builds on previous methods to consider the spatial proximity of utilization distributions, rather than the amount of overlap exclusively (Kranstauber et al. ).…”
Section: Moving Forward: Developing Quantitative Assessment Of Large mentioning
confidence: 99%
“…) and patterns of animal space use and movement (Shamoun‐Baranes et al . ; Kranstauber, Smolla & Safi ). Closer to the current work, they have also been used to compare trait distributions between populations (Gregorius, Gillet & Ziehe ) and to measure the convergence of trait distributions under selection (Rudnicki & Zwoleński ; Zwoleński ).…”
Section: Glossary Of Termsmentioning
confidence: 99%